PENGUATAN KEPERCAYAAN DIRI DAI MAHASISWA MELALUI PELATIHAN PUBLIC SPEAKING BERBASIS ISLAM WASATHIYAH DI UNIVERSITAS AL-FALAH AS-SUNNIYAH - Rizqiyah Ratu Balqis; Imra’atus Shalihah; Riadi Hartono (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity aims to strengthen the self-confidence of student preachers (dai mahasiswa) in delivering Islamic preaching (dakwah) through a public speaking training program grounded in the values of Islam wasathiyah(moderate Islam). The activity was carried out as part of the Islam Wasathiyah Student Preacher Workshop (Workshop Dai Mahasiswa Islam Wasathiyah), organized by Universitas Al-Falah As-Sunniyyah (UAS) Kencong Jember in collaboration with the Agency for Religious Moderation and Human Resource Development (BMBPSDM) of the Ministry of Religious Affairs of the Republic of Indonesia. The core challenge addressed was the persistently low self-confidence of prospective student preachers particularly those designated for deployment to underdeveloped, remote, and frontier regions (3T areas) in speaking before an audience, as well as their limited capacity for moderate and adaptive dakwah communication. The method employed was participatory training with a descriptive quantitative approach, utilizing a pre-test and post-test design. The activity was conducted over three days involving approximately 30 student participants. The training process encompassed material delivery, limited practice sessions, and evaluation through observation as well as pre-test and post-test results to measure changes in participants' self-confidence levels. The results demonstrated an improvement in students' self-confidence in presenting ideas before an audience, although technical competencies in audience engagement and message delivery still require further development. In addition, participants showed a better understanding of the importance of moderate, inclusive, and contextually sensitive dakwah communication in a diverse society. The implications of this activity suggest that public speaking training grounded in Islam wasathiyah values can serve as an effective strategy for strengthening the capacity of student preachers. The originality of this activity lies in its integration of public communication skills training with the reinforcement of religious moderation values in the context of student preacher development within higher education institutions.